Signless Laplacian Energy of Operations on Intuitionistic Fuzzy Graphs - Ramesh, Obbu; Sharief Basha, S.; Abdul Hameed, W. (International Journal of Engineering and Technology, 2018)
After determining the  Signless Laplacian energy of an Intuitionistic fuzzy graphs and the study of lower and upper boundaries of Signless Laplacian energy of an Intuitionistic fuzzy graphs, then we planned to search Signless Laplacian energy of an Intuitionistic fuzzy graphs on some operations such as Union and Join of the Intuitionistic Fuzzy Graphs and also examine the difference between two Intuitionistic fuzzy graphs.